Principals’ leadership styles as predictors of teachers’ attitude toward parental involvement - Barth, Anat; Tsemach, Sigalit (Frontiers in Education, 2025)
IntroductionParental involvement has become a key component of school success. Both in terms of organizational functioning and students’ individual excellence. Many factors influence parental involvement, one of which is teachers’ attitudes toward it. The way teachers address parental involvement is shaped by personal, professional, cultural, and organizational characteristics. The current study explores the influence of principals’ leadership styles (i.e., transformational, authentic, and participative) on teachers’ attitudes toward parental involvement, and identifies which styles are the most effective predictors of positive attitudes of the latter.MethodsSix hundred and twenty-two teachers completed an online questionnaire distributed through social media.ResultsStepwise Linear Regression revealed that participative leadership is a main contributor to positive teachers’ attitudes toward parental involvement. Authentic leadership also contributes positively to these attitudes, while transformational leadership does not predict regarding these attitudes at all.DiscussionThe results suggest that empowering teachers in school processes and fostering an ethical climate are mechanisms that allow principals to improve teachers’ attitudes toward parental involvement. However, focusing on inspiration, individual consideration, intellectual stimulation, or functioning as a role model does not effectively improve these attitudes. These findings may be attributed to the organizational security that participative and authentic leadership provide, and to the fact that transformational leadership, which fosters personal commitment, does not address external challenges such as interactions with parents. In practice, understanding the unique contributions of each leadership style can help principals choose the appropriate actions to address specific organizational challenges. In conclusion, overall, the study highlights the importance of participative and authentic leadership in promoting positive teacher attitudes toward parental involvement, which is crucial for school success.